2011
DOI: 10.1021/tx2001042
|View full text |Cite
|
Sign up to set email alerts
|

Acute, Sublethal Cyanide Poisoning in Mice Is Ameliorated by Nitrite Alone: Complications Arising from Concomitant Administration of Nitrite and Thiosulfate as an Antidotal Combination

Abstract: Sodium nitrite alone is shown to ameliorate sub-lethal cyanide toxicity in mice when given from ~1 hour before until 20 minutes after the toxic dose as demonstrated by the recovery of righting ability. An optimum dose (12 mg/kg) was determined to significantly relieve cyanide toxicity (5.0 mg/kg) when administered to mice intraperitoneally. Nitrite so administered was shown to rapidly produce NO in the bloodsteam as judged by the dose dependent appearance of EPR signals attributable to nitrosylhemoglobin and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
87
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(92 citation statements)
references
References 49 publications
(95 reference statements)
4
87
1
Order By: Relevance
“…We attempted a few experiments in which the Co III TMPyP was given 2 min following the cyanide, obtaining righting recovery times that were comparable to controls, but less reproducible (not shown) and these were not continued to statistical significance. In contrast, in a previous study 6 we showed that sodium nitrite was markedly antidotal if given 2 min after the cyanide (reproduced as the last column in Figure 6). Collateral deaths in these experiments occurred between 1.5 and 3 min and behavioral indications of toxicity were already apparent 1 min after injection of the cyanide, suggesting the toxic dose to have become systemically distributed by 1 min onwards.…”
Section: Discussioncontrasting
confidence: 89%
See 4 more Smart Citations
“…We attempted a few experiments in which the Co III TMPyP was given 2 min following the cyanide, obtaining righting recovery times that were comparable to controls, but less reproducible (not shown) and these were not continued to statistical significance. In contrast, in a previous study 6 we showed that sodium nitrite was markedly antidotal if given 2 min after the cyanide (reproduced as the last column in Figure 6). Collateral deaths in these experiments occurred between 1.5 and 3 min and behavioral indications of toxicity were already apparent 1 min after injection of the cyanide, suggesting the toxic dose to have become systemically distributed by 1 min onwards.…”
Section: Discussioncontrasting
confidence: 89%
“…We interpret the more rapid action of sodium nitrite to be a consequence of its ability to directly protect cytochrome c oxidase from inhibition within the mitochondrion. 6 Scavengers like Co III TMPyP must work more passively by binding available cyanide in the circulating bloodstream, or as may have been the case to some extent in the present experiments, any remaining within the intraperitoneal cavity.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations